Increased expression of progesterone receptor membrane component 1 is associated with aggressive phenotype and poor prognosis in ER-positive and negative breast cancer. Issue 2 (February 2017) - Ruan, Xiangyan; Zhang, Ying; Mueck, Alfred O.; Willibald, Marina; Seeger, Harald; Fehm, Tanja; Brucker, Sara; Neubauer, Hans
Abstract: Objective: Expression of progesterone receptor membrane component 1 (PGRMC1) has been shown to be higher in breast cancer than normal tissue. We have previously shown that certain progestogens strongly stimulate proliferation of breast cancer cells overexpressing PGRMC1, and therefore hypothesize that PGRMC1 may play a critical role in breast cancer progression. Because little information is available if expression of PGRMC1 is also associated with worse prognosis for breast cancer patients, in this study we investigated the clinicopathologic significance of PGRMC1 expression in breast cancer tissue. Methods: Expression of PGRMC1 was analyzed by immunohistochemical staining of primary tumor tissues obtained from 69 breast cancer patients. A labeling score was developed, and results were correlated with tumor size, lymph node metastasis, and clinical outcome. Results: Overexpression of PGRMC1 is correlating with larger tumor size and lymph node metastasis. Kaplan-Meier survival curves indicate that patients with PGRMC1 high tumors have poorer disease-free and overall survival independent from the estrogen receptor status than breast cancer patients with PGRMC1 low tumors. Conclusions: Our findings suggest that the expression of PGRMC1 might be useful for predicting prognosis in patients with breast cancer.